Multi-Tenant Architecture: A Comprehensive Framework for Building Scalable SaaS Applications - Shinu Pushpan, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Multi-tenant architecture has emerged as a fundamental paradigm in modern software development, particularly in Software as a Service (SaaS) applications where multiple organizations share computing resources while maintaining data isolation. This article presents a comprehensive framework for understanding and implementing multi-tenant systems, focusing on essential architectural decisions and design patterns that ensure scalability, security, and resource efficiency. The article examines the evolution from single-tenant to multi-tenant architectures, analyzes various data partitioning strategies, and explores critical aspects of tenant isolation, authentication, and authorization mechanisms. The article addresses key challenges in performance optimization, resource allocation, and security implementation, providing practical insights into database design approaches and caching strategies. Through a structured approach, this article bridges the gap between theoretical concepts and practical implementation, offering developers and architects a foundation for building robust multi-tenant systems. The findings emphasize the importance of balanced architectural decisions that accommodate both technical requirements and business objectives while maintaining system integrity and tenant isolation. This article contributes to the growing body of knowledge in cloud computing and distributed systems, providing practitioners with actionable insights for developing scalable multi-tenant applications.
Keywords: Multi-tenant Architecture; Software as a Service (SaaS); Data Isolation; Scalable Systems; Cloud Computing Architecture